2008
DOI: 10.1177/0885066608324208
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Organ Donor Management Protocol

Abstract: As of August 2007, 96 900 people are awaiting organ transplantation in the United States, while only 28 930 transplants were performed in 2006. With such a large gap between organ need and organ availability, it is inevitable that many will die while awaiting transplantation. This organ shortage has become a national public health crisis, and as a response, the United States Department of Health and Human Services launched the Organ Donation Breakthrough Collaborative, an ambitious campaign to dramatically inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 77 publications
0
49
0
2
Order By: Relevance
“…1D). However, the frequency of CD141 + cDC and the CD304 + pDC recovered from total splenocytes from cardiac death donors was markedly reduced, consistent with the recognized inferior quality of cardiac death tissues (30). Because of this, and because of the rarity of non-MP-treated donors, our focus was on DC from braindead organ donor spleens.…”
Section: Cd304mentioning
confidence: 69%
See 1 more Smart Citation
“…1D). However, the frequency of CD141 + cDC and the CD304 + pDC recovered from total splenocytes from cardiac death donors was markedly reduced, consistent with the recognized inferior quality of cardiac death tissues (30). Because of this, and because of the rarity of non-MP-treated donors, our focus was on DC from braindead organ donor spleens.…”
Section: Cd304mentioning
confidence: 69%
“…We used deceased organ donors in which life-support was maintained prior to brain death, resulting in optimal quality of the tissue (30). We developed new methods to isolate and functionally characterize DC subsets from spleen for a comprehensive comparison of all human spleen and blood DC subsets, and addressed organ donor-related effects on DC.…”
Section: Endritic Cells (Dc) Process and Present Self And Foreignmentioning
confidence: 99%
“…The respiratory management of a potential donor is frequently complicated by pulmonary injuries such as the following: neurogenic pulmonary edema, respiratory infections, pulmonary bleeding and traumatic pulmonary injury (D) (6,54,55) (C). (56) The development of atelectasis secondary to the supine position of the deceased donor, the prolonged period of mechanical ventilation and aggressive fluid resuscitation are frequent causes of hypoxemia.…”
Section: Lung Maintenancementioning
confidence: 99%
“…These potential donors need optimized therapeutic support to prevent donor loss and increase the number of viable retrieved organs. 1,2 Extracorporeal membranous oxygenation (ECMO) has been increasingly used as bridge therapy for patients with potentially reversible cardiac or respiratory failure. Normally, patients offered this form of treatment are deemed to have good overall organ status before experiencing acute cardiac or respiratory events.…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant number of patients treated with ECMO do not recover because of either the nonsalvageable nature of their heart or respiratory condition or a neurologic event that sometimes accompanies this form of therapy. [1][2][3] There have been few reports about the outcomes of organs retrieved from patients after treatment with ECMO. Orandi and colleagues (2015) reported that, out of 82 143 deceased-donor kidney transplants, 22 185 (27.0%) recipients developed delayed graft function (DGF).…”
Section: Introductionmentioning
confidence: 99%